Expression of the RNA recognition motif protein RBP10 promotes a bloodstream-form transcript pattern in Trypanosoma brucei - Wurst, Martin; Jha, Bhaskar Anand; Klein, Cornelia Andrea; Clayton, Christine (Molecular microbiology, 2012)
When Trypanosoma brucei differentiates from the bloodstream form to the procyclic form, there are decreases in the levels of many mRNAs encoding proteins required for the glycolytic pathway, and the mRNA encoding the RNA recognition motif protein RBP10 decreases in parallel. We show that RBP10 is a cytoplasmic protein that is specific to bloodstream-form trypanosomes, where it is essential. Depletion of RBP10 caused decreases in many bloodstream-form-specific mRNAs, with increases in mRNAs associated with the early stages of differentiation. The changes were similar to, but more extensive than, those caused by glucose deprivation. Conversely, forced RBP10 expression in procyclics induced a switch towards bloodstream-form mRNA expression patterns, with concomitant growth inhibition. Forced expression of RBP10 prevented differentiation of bloodstream forms in response to cis-aconitate, but did not prevent expression of key differentiation markers in response to glucose deprivation. RBP10 was not associated with heavy polysomes, showed no detectable in vivo binding to RNA, and was not stably associated with other proteins. Tethering of RBP10 to a reporter mRNA inhibited translation, and halved the abundance of the bound mRNA. We suggest that RBP10 may prevent the expression of regulatory proteins that are specific to the procyclic form.